Pengetahuan guru dan tahap kemahiran berfikir aras tinggi (KBAT) pelajar tingkatan 2 dalam topik ungkapan Algebra II - Ibrahim, Mohd. Ali (2014)
This study aimed to investigate the Teachers knowledge of High Order Thinking Skills (HOTS) and the level of High Order Thinking Skills (HOTS) among Form Two Students for Algebra Expression II. The instrument was used in this study is a set of questions to test the students with the reliability of the items, a = .800, and a set of questionnaires to the teachers with the reliability of the items, a = .808. A total of 20 mathematics teachers and 200 students in Sekolah Menengah Zone Senggarang, Batu Pahat Johor involved as respondents in this study. The data collected were analysed using SPSS version 16.0 using descriptive and inferential using t-test. The results showed that most of the teachers understand and know about higher-order thinking skills, but a few of them still not understand about HOTS. The results also showed that there was significant difference between the scores of students across gender at significance level .05 which the level of female is higher than male students. Keywords: Higher order thinking skills (HOTS), Algebra Expression II, Mathematics Education, level of Higher order thinking skills (HOTS) Kata kunci: Kemahiran Berfikir Aras Tinggi, ungkapan algebra II, pendidikan matematik, tahap kemahiran berfikir aras tinggi (KBAT).